Coexistence of Candida albicans and Enterococcus faecalis increases biofilm virulence and periapical lesions in rats. Issue 9 (28th November 2021) - Du, Qian; Yuan, Shasha; Zhao, Shuangyuan; Fu, Di; Chen, Yifei; Zhou, Yuan; Cao, Yangpei; Gao, Yuan; Xu, Xin; Zhou, Xuedong; He, Jinzhi
Abstract: The present study utilized an in vitro dual-species biofilm model and an in vivo rat post-treatment endodontic disease (PTED) model to investigate whether co-infection of Candida albicans and Enterococcus faecalis would aggravate periapical lesions. The results showed that co-culturing yielded a thicker and denser biofilm more tolerant to detrimental stresses compared with the mono-species biofilm, such as a starvation-alkalinity environment, mechanical shear force and bactericidal chemicals. Consistently, co-inoculation of E. faecalis and C. albicans significantly increased the extent of in vivo periapical lesions compared with mono-species infection. Specifically, coexistence of both microorganisms increased osteoclastic bone resorption and suppressed osteoblastic bone formation. The synergistic effects also up-regulated inflammatory cytokines including TNF-α and IL-6 . In summary, coexistence of C. albicans and E. faecalis increased periapical lesions by enhanced biofilm virulence.